Health education intervention regarding swine flu among secondary school students in a selected school of Dhaka city (Northern International Medical College Journal, 2015)
Background : Swine flu is a viral disease spread by droplet infection during coughing, sneezing, laughing or talking. Mortality rate among the adolescent is high.Objective : To assess the outcome of health education intervention on knowledge regarding Swine flu among adolescent students of a selected school in Dhaka city.Material & Methods : A quasi-experimental study was conducted among 150 students of class × of B.C.S.I.R. High School in Dhaka city. As Dhaka city is densely populated and chance of transmission Swine flu is higher.Results : The mean age of the students was 14.83 years. Regarding educational qualification of their mothers, 40% had completed education up to the S.S.C level. In case of occupational status of the fathers, 50.7% were businessmen. A majority (31.3%) of the respondents had monthly income of 20,001-30,000 Taka. Almost all (99.3%) of the students had heard the name of Swine flu and their source of information was from newspapers (50.5%) followed by that of television (26.2%),family members (8.1%) and radio(4.7%). Before intervention- regarding the causative agent & mode of transmission, 75.3% & 92.0% of the students had a good knowledge respectively. Fair knowledge was observed among the students regarding signs & symptoms (50.7%), complications (46.0%) and preventive measures (51.3%) of the disease. Poor knowledge was found regarding high risk groups of the disease among 52% of respondents. A high proportion of respondents, (94.0%) had no knowledge regarding treatment of Swine flu. In case of overall knowledge regarding Swine flu, 27.3% had poor knowledge; 56.7% had fair knowledge and 16.0% had good knowledge before intervention. After health education intervention 98.7% & 1.37 of students had good & fair level of knowledge regarding the disease respectively no respondent was observed poor knowledge. Chi square test (x2=2.096, df=2) showed the significant association (p